A better way of life: The role of leisure activities on self-perceived health, perceived stress, confidence in stress management, and satisfaction with social support in psychiatrists and psychiatry trainees in Mexico - Lagunes-Córdoba, Emmeline; Yoldi-Negrete, María; Hewson, Tom; Guízar-Sánchez, Diana; Robles-García, Rebeca; Tovilla-Zárate, Carlos Alfonso; Tracy, Derek; Saracco-Alvarez, Ricardo Arturo; Fresán, Ana (Frontiers in Psychiatry, 2022)
Background: Psychiatrists are at high risk of developing burnout and mental health problems mainly due to their emotionally demanding jobs, difficult working conditions, long working hours, and poor work-life balance. As leisure activities are associated with better physical and mental health, engaging in these activities has been recommended as a measure to improve the wellbeing of healthcare workers. However, it is unclear the extent of which psychiatrists and trainees are involved in leisure activities, what type of activities they prefer, or how these impact their self-perceived health, stress, confidence in stress management, and satisfaction with their social support. Objective: The aim of this study was to identify differences in self-perceived health, perceived stress, confidence in stress management, and satisfaction with social support, between psychiatrists and trainees who engage in different leisure activities, compared with those who do not. Method: This was a cross-sectional study, including Mexican psychiatrists (n=355) and trainees (n=330) who agreed to participate through an online survey. Results: 73.1% of participants engaged in some leisure activity, being solitary-passive activities the most reported. Those who have a leisure activity reported lower stress, greater confidence in stress management, and more satisfaction with their social support. Passive-solitary activities were associated with less perceived stress and better confidence in stress management, while active-solitary and social activities were associated with better satisfaction with social support. Conclusion: Psychiatrists’ and trainees’ wellbeing benefits from engagement in leisure activities, which should be part of their daily schedules to reduce stress, and potentially improve their mental health.